2017
DOI: 10.1021/acs.energyfuels.6b02602
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Study of Depositional Paleoenvironments and Organic Matter Inputs for Permian Coalbearing Strata in the Huaibei Coalfield, East China

Abstract: This study presents detailed information regarding the organic geochemical and biomarker characteristics of the Permian coal-bearing strata in the Huaibei coalfield. The type of organic matter, sources input, depositional paleoenvironments, and thermal maturity are revealed by the organic molecular signatures study. These are of great significance to understand the coalification process and the generation of the coalbed methane. The extractable organic matter (EOM) in coal and coaly mudstone samples are 1.14% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…The valence state of Ce and Eu changes when the environment changes, so the Ce anomaly (δCe) and Eu anomaly (δEu) can be used as indicators for determining the sedimentary environment (Li, Ju, et al, 2017;Wang, Chen, et al, 2020). The anomalies of Ce and Eu in all mudstone samples are between 1, with average values of 0.98 and 0.97, indicating an oxic-anoxic deposition environment.…”
Section: Palaeoredox Conditionsmentioning
confidence: 99%
“…The valence state of Ce and Eu changes when the environment changes, so the Ce anomaly (δCe) and Eu anomaly (δEu) can be used as indicators for determining the sedimentary environment (Li, Ju, et al, 2017;Wang, Chen, et al, 2020). The anomalies of Ce and Eu in all mudstone samples are between 1, with average values of 0.98 and 0.97, indicating an oxic-anoxic deposition environment.…”
Section: Palaeoredox Conditionsmentioning
confidence: 99%
“…Tight sandstone gas in some gas fields was thought to partly originate from carbonate because stable carbon isotope compositions indicate a coal-derived gas mixed with an amount of oil-derived gas (Dai et al, 2005;. However, because the sediments were deposited in a marine-continental transitional environment, a certain amount of OM in mudstone was sourced from marine aquatic-derived OM (Li Q et al, 2017;Qi et al, 2019aQi et al, , 2019b. As such, we believe that the oil-derived gas may partly originate from these transitional mudstones.…”
Section: Source Rocks and Gas Generation Conditionsmentioning
confidence: 91%
“…is generally used as a maturation parameter. [63][64][65][66] However, previous studies 67,68 have indicated that acidic (presence of clay minerals) or strongly oxidizing conditions catalyze conversion reactions from regular steranes to diasteranes, being related to deltaic marine deposition environments. In oil samples from evaporative carbonate or marine sources, diasteranes are in low relative abundance or even absent.…”
Section: Depositional Environment and Redox Conditionsmentioning
confidence: 99%